Changes in social interaction, social relatedness, and friendships in Education Outside the Classroom: A social network analysis - Ellinger, Jan; Mess, Filip; Bachner, Joachim; von Au, Jakob; Mall, Christoph (Frontiers in Psychology, 2023)
Social interaction is associated with many effects on the psychological level of children such as mental health, self-esteem, and executive functions. Education Outside the Classroom (EOtC) describes regular curricular classes/lessons outside the school building, often in natural green and blue environments. Applied as a long-term school concept, EOtC has the potential to enable and promote social interaction. However, empirical studies on this topic have been somewhat scant. One class in EOtC (N = 24) and one comparison class (N = 26) were examined in this study to explore those effects. Statistical Actor-Oriented Models and Exponential Random Graph Models were used to investigate whether there are differences between EOtC and comparison class regarding changes over time in social interaction parameters; whether a co-evolution between social interaction during lessons and breaks and attendant social relatedness and friendships exists; whether students of the same gender or place of residence interact particularly often (homophily). Besides inconsistent changes in social interaction parameters, no co-evolutional associations between social interaction and social relatedness and friendships could be determined, but grouping was evident in EOtC. Both classes showed pronounced gender homophily, which in the case of EOtC class contributes to a fragmentation of the network over time. The observed effects in EOtC could be due to previously observed tendencies of social exclusion as a result of a high degree of freedom of choices. It therefore seems essential that in future studies not only the quality of the study design and instruments should be included in the interpretation - rather, the underlying methodological-didactic concept should also be evaluated in detail. At least in Germany, it seems that there is still potential for developing holistic concepts with regards to EOtC in order to maximize the return on the primarily organizational investment of implementing EOtC in natural environments.